Use of local reactive aggregate for geopolymer concrete production - Fu, Jiajun (2017)
The demand for concrete has grown considerably over the last decades, in line with the population growth and the need for more infrastructures. Therefore, the environmental impacts on the high-volume extraction of natural resources and the sources of aggregate available for manufacturing of Ordinary Portland Cement (OPC) and concrete respectively are of major concern. Geopolymerization is a general term used to describe the chemical processes that are involved in activating aluminosilicates with alkaline solutions to produce inorganic binders called geopolymers. Geopolymers are materials that has the potential to be used in many broad applications, including the use as a substitute for OPC. The synthetic alkali aluminosilicate structure of geopolymer results in a wide range of materials that can be synthesized together, a variety of aluminosilicate bearing raw materials such as fly ash from industrial by product from coal burning plants could be used. In order not to further aggravate the environmental implications caused by concrete industry, structures built should be durable over its expected life. The aggregates used in concrete production plays a significant role in the durability of the concrete produced due to the presence of alkali-silica reaction (ASR). However not all countries have the availability of truly non-reactive aggregate that matches the demand for concrete required for the rapid development. Therefore, the use of ASR reactive aggregate is inevitable and other ways of overcoming ASR should be developed. Fly ash is a promising cementitious material to replace OPC binder for concrete production using reactive aggregate. However, the potential durability concern of ASR occurring in fly ash geopolymer concrete (FAGC) cannot be eliminated due to the presence of high alkalinity activating solution and reactive aggregates used. In this experimental study, Accelerated Mortar Bar Test (ASTM C 1260) and Concrete Prisms Test (ASTM C 1293) were employed to evaluate the potential reactivity of aggregate used and to assess the ASR induced expansion in FAGC when paired with reactive aggregates. The reactive aggregate used is a type of sedimentary rock excavated in Singapore and stockpiled in abundance at Jurong Island due to its ASR reactivity. This report presents the measured expansions in geopolymer were all well below the threshold, suggesting innocuous ASR performance. The mechanisms responsible for absence of ASR were explored and determined to be due to the rapid reduction of alkalinity in pore solution to below ASR initiating value at early age.